2009
DOI: 10.1016/j.brainres.2009.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Descending glutamatergic pathways of PFC are involved in acute and chronic action of methylphenidate

Abstract: Progressive augmentation of behavioral response following repeated psychostimulant administrations is known as behavioral sensitization, and is an indicator of a drug’s liability for abuse. It is known that methylphenidate (MPD) (also known as Ritalin), a drug used to treat Attention-Deficit Hyperactivity Disorder (ADHD), induces sensitization in animals following repeated injections. It was recently reported that bilateral electric (non-specific) lesion of prefrontal cortex (PFC) prevented MPD elicited behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…Previous studies suggest that glutamatergic pathways are involved in the acute and chronic MPH regulation of locomotion in adult rats (61), and exposing rats to MPH during adolescence period results in increased stress reactivity (7). It awaits to be tested whether PFC network activity is altered after long-term exposure to different doses of MPH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that glutamatergic pathways are involved in the acute and chronic MPH regulation of locomotion in adult rats (61), and exposing rats to MPH during adolescence period results in increased stress reactivity (7). It awaits to be tested whether PFC network activity is altered after long-term exposure to different doses of MPH.…”
Section: Discussionmentioning
confidence: 99%
“…The 6-OHDA was dissolved in 2 μl of 0.9% saline containing 0.2 mg/ml ascorbic acid (Jackson, 1983; Wanchoo et al, 2009). The cannula was left in place for additional three minutes after the completion of each injection to allow diffusion of the 6-OHDA to the surrounding tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Bilateral ablation of the PFC and nucleus accumbens (NAc) by electrolytic lesion has been reported to prevent the expression of behavioral sensitization produced by repetitive psychostimulant administration (Lee, 2008; Podet et al, 2010; Tang, 2009). Similarly, bilateral injection of 6-hydroxydopamine (6-OHDA) into the PFC and NAc that specifically eliminated the dopaminergic system in these areas has shown to prevent the behavioral sensitization produced by chronic administration of MPD (Wanchoo et al, 2009). Another experiment investigating the effect of amphetamine induced taste aversion before and following 6-OHDA injection reported that 6-OHDA treated animals exhibit attenuation to the aversion preference assay (Roberts and Fibiger 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The three treatment dosages 0.6 mg/kg, 2.5 mg/kg, and 10.0 mg/kg of MPD-D chosen in this study were based on our previous dose response studies. Chronic treatment with 2.5 mg/kg and, in a few cases, also the 0.6 mg/kg MPD dose elicited behavioral sensitization (Gaytan et al 1996a, 1997a, 2000a, 2000b; Lee et al 2008; Wanchoo et al 2009; Yang et al 2000a, 2001, 2000b, 2003, 2006a, 2006b, 2007). The doses in the present study correlate to low, medium, and high doses, respectively (Dafny and Yang 2006).…”
Section: 0 Methodsmentioning
confidence: 96%